Avaliação do status taxonômico e análise populacional de Clyomys bishopi, um roedor endêmico dos Cerrados do estado de São Paulo - Arantes, Ana Carolina Ramos (Universidade Federal de São Carlos, 2011)
Cerrado is one of the brazilian biomes with the highest concentration of species and endemism, and is considered a hotspot of global biodiversity. Only 20% of its original area remains intact in the country and has been permanently transformed by human actions, which makes this biome a priority area for conservation. Due to the great loss of habitat and biodiversity, it is necessary to increase knowledge of basic characteristics of the existing species. Conservation genetics makes use of the genetic variation to infer the taxonomic status and life history of a species, making possible the study of characteristics such as the pattern of social structure and dispersion. Thus, basic data from species to which we have difficult assess can be accessed and better conservation strategies can be adopted. Mitochondrial and nuclear markers are important tools for studies of genetic and social structure in animals. In this study we assessed the taxonomic status of Clyomys bishopi, a colonial and semi-fossorial rodent inhabiting the Cerrado of São Paulo, and also the social and spatial genetic structure of individuals collected in the Estação Ecológica de Itirapina- SP. To evaluate C. bishopi taxonomic status we analyzed the cytochrome b gene of 21 individuals belonging to the genus and from various localities of its distribution. Phylogenetic methods based on Bayesian Inference, Maximum Parsimony and Neighbor-Joining showed high values of branch support separating individuals from São Paulo with respect to the rest of the samples, and genetic distance of about 4% between these groups, suggesting a significant genetic separation between them. For population analysis, ten microsatellite loci were isolated and characterized within C. bishopi. Through the analysis of 40 individuals sampled at three areas within EE de Itirapina, we verified high levels of genetic diversity (NA = 10, average HO = 0,76 and averaged HE = 0,90). Nine microsatellite loci and the control region of the mitochondrial DNA were used to assess the spatial and social genetic structure of the EE de Itirapina population. The Bayesian clustering analysis indicated no genetic structure, suggesting the occurrence of gene flow between sampled areas. Relatedness analyses indicated, in general, low relatedness indices between analyzed individuals (0.05), with slightly larger values when only individuals in a small geographic scale are considered. The average relatedness by sex indicated no significant differences, suggesting similar dispersion between males and females. Results suggest that colonies of Clyomys bishopi are composed largely by unrelated individuals, and present genetic structure compatible to that showed by species with solitary habits.
Keywords: Genética; Clyomys bishopi; Diversidade genética; Taxonomia; Estrutura populacional; Estrutura social; Clyomys bishopi; Genetic diversity; Taxonomy; Population structure; Social structure; CIENCIAS BIOLOGICAS::GENETICA